The Influence of Live Streaming, Price Discount, and Shopping Lifestyle on Impulsive Buying Behavior Among Shopee App Users: A Study on West Jakarta Society - Amanda Aurelia; Daru Asih (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study investigates the influence of live streaming, price discounts, and shopping lifestyle on impulsive buying behavior among Shopee users in West Jakarta. The research is motivated by the growing trend of e-commerce activities and the need to understand consumer behavior in digital shopping environments. A quantitative research design was employed, using purposive sampling methods to survey 160 Shopee users through online questionnaires. The variables analyzed include live streaming, price discount, shopping lifestyle as independent variables, and impulsive buying as the dependent variable. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess validity, reliability, and structural path relationships. The findings reveal that shopping lifestyle has a significant and positive effect on impulsive buying behavior, indicating that individuals with a higher propensity for shopping are more likely to make unplanned purchases. However, live streaming and price discount were found to have no significant impact on impulsive buying. This suggests that while marketing strategies like live streaming and discounts are widely used, their effectiveness in triggering impulse buying is limited unless aligned with consumers’ shopping lifestyles. The study emphasizes the importance for marketers and platform managers to target segments with high shopping lifestyles and develop campaigns that appeal to emotional and habitual aspects of shopping. Future research is suggested to expand the sample size and geographic scope for broader generalizability. The study contributes to the literature on digital consumer behavior and offers practical insights for e-commerce practitioners aiming to boost impulsive purchases.